Challenges and Expectations in Reading English Poetry: A Study of Nepali Undergraduates (Rupandehi Campus Journal, 2025)
This study explores challenges faced by undergraduate students in reading English poetry in an ESL context. Nine purposively selected students from a community campus in Nepal were interviewed. Findings reveal major difficulties including poor reading habits, limited vocabulary, unfamiliar poetic devices, and lack of contextual understanding. These challenges were identified as linguistic, cultural, and cognitive. Participants expected teachers to provide explanations of context, clarify poetic devices, and create opportunities for aesthetic appreciation. The study emphasizes the importance of student-centered, interactive approaches to poetry instruction, encouraging deeper engagement through improved reading strategies, contextual interpretation, and poetic analysis.